2011
DOI: 10.1175/jcli-d-10-05014.1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of SSTA in the East Indian Ocean on the Frequency of Northwest Pacific Tropical Cyclones: A Regional Atmospheric Model Study

Abstract: The impact of the sea surface temperature anomaly (SSTA) in the East Indian Ocean (EIO) on the tropical cyclone (TC) frequency over the western North Pacific (WNP) and the involved physical mechanisms are examined using the International Pacific Research Center (IPRC) Regional Atmospheric Model (iRAM) driven by the reanalysis and the observed SSTs. The model reproduces generally quite realistic climatic features of the WNP TC activity, including the interannual variability of the WNP TC genesis frequency, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
56
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(60 citation statements)
references
References 36 publications
4
56
0
Order By: Relevance
“…These TC anomalies are captured in highresolution AGCM simulations, pointing to the importance of SST boundary conditions (Mei et al, 2015). Using a regional atmospheric model, Zhan et al (2011) showed that eastern IO SST anomalies affect TC genesis over the TNW Pacific by modulating the western Pacific summer monsoon via the equatorial Kelvin wave.…”
Section: Northwest Pacific Tcs and Indian Rainfallmentioning
confidence: 98%
“…These TC anomalies are captured in highresolution AGCM simulations, pointing to the importance of SST boundary conditions (Mei et al, 2015). Using a regional atmospheric model, Zhan et al (2011) showed that eastern IO SST anomalies affect TC genesis over the TNW Pacific by modulating the western Pacific summer monsoon via the equatorial Kelvin wave.…”
Section: Northwest Pacific Tcs and Indian Rainfallmentioning
confidence: 98%
“…In the Atlantic, the upward trend in SST is highly correlated with the increase in the intensity of hurricane activity (Webster et al 2005;Emanuel 2005). Although the variability of typhoons is negatively correlated with the local SST (Chan 2006), the SST variations in both the tropical eastern Pacific (i.e., El Niño-Southern Oscillation) and Indian Ocean have been reported to play an important role in the interannual variability of TCs (e.g., Wang and Chan 2002;Camargo et al 2007;Zhan et al 2011;Du et al 2011). Recently, Jin et al (2013) showed that the off-equatorial SST warming over the central Pacific provides a favorable environment for TC motion toward East Asia during the central Pacific El Niño events.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, a better understanding of TC variability and its factors, and improved predictability of TC activity, are of great importance to society. It has been demonstrated that the TC variability over the western North Pacific (WNP) is significantly influenced by SST anomalies over the tropical central-eastern Pacific (e.g., Chan, 1985;Chen et al, 1998;Wang and Chan, 2002;Chan, 2005;Chen and Huang, 2008;Yeh et al, 2010;Cao et al, 2014a;Hsu et al, 2014) and over the Indian Ocean (Zhan et al, 2011). Studies have also indicated that atmospheric circulation systems can influence TC activity over the WNP, such as the stratospheric quasi-biennial oscillation (Chan, 1995;Ho et al, 2009), the Antarctic Oscillation (Ho et al, 2005), and the North Pacific Oscillation (Wang et al, 2007).…”
Section: Introductionmentioning
confidence: 99%